Por uma prática feminista transnacional contra a guerra - Bacchetta, Paola; Campt, Tina; Grewal, Inderpal; Kaplan, Caren; Moallen, Minoo; Terry, Jennifer (Revista Estudos Feministas, 2001)
Por uma prática feminista transnacional contra a guerra